Routine screening for hepatitis C in pregnancy is cost‐effective in a large urban population in Ireland: a retrospective study. (20th November 2021) - McCormick, CA; Domegan, L; Carty, PG; Drew, R; McAuliffe, FM; O'Donohoe, O; White, N; Garvey, P; O'Grady, M; De Gascun, CF; McCormick, PA
Abstract : Objective: To investigate whether risk factor‐based screening in pregnancy is failing to identify women with hepatitis C virus (HCV) infection and to assess the cost‐effectiveness of universal screening. Design: Retrospective study and model‐based economic evaluation. Setting: Two urban tertiary referral maternity units, currently using risk factor‐based screening for HCV infection. Population: Pregnant women who had been tested for hepatitis B, HIV but not HCV. Methods: Anonymised sera were tested for HCV antibody. Positive sera were tested for HCV antigen. A cost‐effectiveness analysis of a change to universal screening was performed using a Markov model to simulate disease progression and Monte Carlo simulations for probabilistic sensitivity analysis. Main outcome measures: Presence of HCV antigen and cost per quality‐adjusted life year (QALY). Results: In all, 4655 samples were analysed. Twenty had HCV antibodies and five HCV antigen. This gives an active infection rate of 5/4655, or 0.11%, compared with a rate of 0.15% in the risk‐factor group. This prevalence is 65% lower than a previous study in the same hospitals from 2001 to 2005. The calculated incremental cost‐effectiveness ratio (ICER) for universal screening was €3, 315 per QALY gained. Conclusion: This study showed that the prevalence of HCV infection in pregnant women in the Dublin region has declined by 65% over the past two decades. Risk factor‐based screening misses a significant proportion of infections. A change to universal maternal screening for hepatitis C would be cost‐effective in our population. Tweetable abstract: Universal maternal screening for hepatitis C is cost‐effective in this urban Irish population. Tweetable abstract: Universal maternal screening for hepatitis C is cost‐effective in this urban Irish population.